CCDC6: the identity of a protein known to be partner in fusion. Issue 7 (26th October 2017) - Cerrato, Aniello; Merolla, Francesco; Morra, Francesco; Celetti, Angela
Abstract : Coiled Coil Domain Containing 6 gene, CCDC6, was initially isolated as part of a tumorigenic DNA originated by the fusion of CCDC6 with the tyrosine kinase of RET receptor, following a paracentric inversion of chromosome 10. For a long time, CCDC6 has been considered as an accidental partner of the RET protooncogene, providing the promoter and the first 101 aa necessary for the constitutive activation of the oncogenic Tyrosine Kinase (TK) RET in thyroid cells. With the advent of more refined diagnostic tools and bioinformatic algorithms, an exponential growth in fusion genes discoveries has allowed the identification of CCDC6 as partner of genes other than RET in different tumor types. CCDC6 gene product has a proper role in sustaining the DNA damage checkpoints in response to DNA damage. The inactivation of CCDC6 secondary to chromosomal rearrangements or gene mutations could enhance tumor progression by impairing the apoptotic response upon the DNA damage exposure, contributing to the generation of radio‐ and chemoresistance. Preclinical studies indicate that the attenuation of CCDC6 in cancer, while conferring a resistance to cisplatinum, sensitizes the cancer cells to the small molecule inhibitors of Poly (ADP‐ribose) polymerase (PARP1/2) with a synthetic lethal effect. Several CCDC6 mutations and gene rearrangements have been described so far in different types of cancer and CCDC6 may represent a possible predictive biomarker of tumor resistance to the conventional anticancer treatments. Nevertheless, the detection of a CCDC6 impairment in cancer patients may help to select, in future clinical trials, those patients who could benefit of PARP‐inhibitors treatment alone or in combination with other treatments.